PRINCIPLES OF TIMELY COMPLEX THERAPY FOR RHEUMATOID ARTHRITIS IN PRESCHOOL CHILDREN - Khafizova Земфира (International Journal of Scientific Pediatrics, 2023)
Abstract: Juvenile rheumatoid arthritis (JRA) of preschool age is represented in the literature by a few observations[1,2]. The purpose of this work was to study the clinical and laboratory signs of the initial period of JRA in 60 children under the age of 7 years, as well as the tactics of rational therapy and the results of follow-up observation of sick preschool children treated in a hospital during 2015-2021. Material and methods: Among the observed patients, the disease began in the majority (32) at the 7th year of life, in 11 - before the age of 5 years, in 17 - at 3 years. Subacute onset of the disease, characteristic of preschool children, was noted in 36 (60%), which was due to the development of the articular form in the majority of patients (39, or 65%). Among them, the majority were children with the most benign variants - oligoarthritis (19) and monoarthritis (5); 15 patients had multiple joint damage. On the contrary, among patients with the articular-visceral form (20, or 33.3%), the most severe variants with polyvisceritis initially prevailed in most cases - allergic septic syndrome (in 10) and Still’s syndrome (in 5). Results: Our observations revealed a certain dependence of the nature of the activity of JRA and the development of destructive changes in the joints on the timing of the start of targeted therapy. Conclusion: therefore, targeted complex long-term therapy of RA in preschool age not only leads to a persistent decrease in activity, stabilization of the process in the majority children, but also avoids the use of corticosteroids, and also promotes reparative changes and rehabilitation of a significant part of patients (43%).